The effect of build orientation and testing temperature on mechanical properties of polyamide-12 printed by multi jet fusion - Muhammad Fithri Bin Sadar (Nanyang Technological University, 2023)
Multi Jet Fusion technology, created by Hewlett Packard (HP), is a form of additive manufacturing (AM) that is currently being researched to enhance its capabilities. It was released in 2016 and can produce large batches of complex parts with reduced costs. Though the technology is new, extensive research has been conducted on how different parameters impact the qualities of the printed parts. Prior studies have revealed that MJF-manufactured parts display greater strength along the Z-axis, and polyamide-12 (PA12) parts have shown to possess higher thermal stability in extreme heat conditions. These factors have been compared to other AM methods to understand the differences in mechanical properties. Studies on the effect of various input parameters on the mechanical properties of MJF-printed PA12 (MJF PA12) have been studied on. However, more research could be explored on how both build orientation and service temperature affects it. This brings to the aim of the project, which was to explore how the build orientation and testing temperature affect the mechanical properties of MJF-printed PA12 parts. The findings were analysed to determine the relationship between the build orientation and temperature of the printed parts. Finally, Scanning Electron Microscopy (SEM) was utilized to analyse the fracture surface of the specimens, allowing for a better understanding of the fracture surface of the parts. It was found that yield stress and Young’s modulus seem to decrease as temperature increases whereas the converse occurs for elongation at break. Additionally, the horizontal build orientation tends to yield higher mechanical properties than the other build orientations.